POLITICAL AND RELIGIOUS DYNAMICS OF ISLAM DURING THE SAFAVID AND MUGHAL DYNASTIES - Muntako Muntako; Kholid Mawardi (LP2M IAI Al-Khairat Pamekasan, 2026)
This study explores the political and religious dynamics of Islam during the Safavid Dynasty in Persia and the Mughal Dynasty in India, using a library research method. Both were major Islamic empires from the 16th to the 18th century that played significant roles in shaping religious identity and systems of Islamic governance in the East. The Safavid Dynasty is known for its theocratic governance and establishment of Twelver Shi’ism as the official state religion, while the Mughal Dynasty is recognized for its pluralistic approach and tolerance of religious diversity. The findings indicate that both dynasties utilized religion as a source of political legitimacy, but with different strategies and consequences. This article offers a conceptual comparison between the exclusive Safavid model and the pluralistic Mughal model, highlighting their relevance to contemporary discussions on Islam and politics.